Etnobotany in Customary Ceremony in Dayak Society, UUD Danum - Hendrikus Julung; Benediktus Ege (Universitas Khairun, 2020)
The Dayak Uud Danum people still maintain the traditional ceremonies of birth, marriage, death and traditional medicine. This tradition is carried out as a tribute to the cultural heritage of the ancestors. This tradition cannot be separated from the use of plants as media which have an important role. However, the effects of globalization can threaten the sustainability of these plants, so an inventory of their existence is needed. This study aims to identify various types of plants used in various customary traditions in the Dayak Uud Danum tribe in Kemangai Village, Ambalau District. The research method used is a survey method with data collection tools in the form of semi-structured interviews. The results showed that there were 6 family of plants used for traditional birth rituals, 3 families for traditional marriage, 5 families for traditional death rituals, and 35 families for traditional medicine. Processing plants for custom births by boiling, drinking and eating. In a wedding ceremony the processing of plants is eaten, wrapped and wrapped. In traditional death rituals, plants are used to make coffins, and statues are symbols of respect for the deceased. As for traditional medicine, most plants are processed by boiling and drinking. The parts of the plants that are most widely used in the four traditional rituals of the Dayak Uud Danum are the leaves, roots and stems.